Competencies in Higher Education System: an Empirical Analysis of Employers` Perceptions - Adela Deaconu; Codruţa Osoian; Monica Zaharie; Sorin Adrian Achim (Amfiteatru Economic)
This study offers insight into the European Qualifications Framework (EQF), as agreed and detailed by the Romanian qualifications framework, applied to the economic sector. By means of a survey conducted on 92 employing companies, it validates the importance of competencies for the Romanian labour market and employers` degree of satisfaction with the competencies of business graduates. In terms of typology, employers attach more importance to transversal competencies than to professional competencies, both at conceptual level and as degree of acquirement following higher education. The empirical analysis provides data on employers` ranking of transversal and professional competencies and identifies the classes of competencies deemed to be in short supply on the labour market. Through its results, the study enhances the relationship between the higher education system and the labour market, providing key information for an efficient implementation of the competence-based education system.